SKABIES DENGAN INFEKSI SEKUNDER PADA PASIEN REMAJA - Agus Pramana (Jurnal Medika Hutama, 2025)
Introduction: Scabies is a skin disease caused by infection and sensitization to Sarcoptes scabiei var. hominis and its by-products. This disease is highly contagious and spreads easily through direct skin contact or shared items used by the patient. The cardinal signs of scabies include nocturnal pruritus, clustered outbreaks in human populations, burrow tracks (cuniculi) at predilection sites, and intense itching, especially at night. Case report: We reported a 15-year-old male patient a one-week history of pruritic erythematous papules located primarily between the fingers of both hands and on the right foot. Family members in the same household reported similar symptoms. The diagnosis of scabies with secondary infection was made. The patient then received topical and systemic therapy followed by hygiene education, and reported improvement. Conclusion: Early recognition and appropriate treatment of scabies, prevent further transmission and complications. This also ensures a favorable outcome and reduction in scabies' impact on affected individuals' quality of life